The Impact of Phentagonal on the Economic Resilience of the South Kuta Community - Kadek, Ariyuni Ni; Ketut, Merta I; Made, Widani Ni (International Journal of Management and Business Intelligence, 2024)
This research took as its object the South Kuta Subdistrict Office, Badung Regency, which aims to examine the Pentagonal Impact on the Economic Resilience of the South Kuta Community using the main theory, namely the grand theory (Van Holk, 2008) which suggests that what forms resilience and these factors interact with each other throughout life. This research uses quantitative methods using a questionnaire and a sample of 92 people from the South Kuta community, as well as five hypotheses using SPSS V 2024 with multiple regression. The results of this research found: 1. Human Resources showed a negative and insignificant influence on the economic resilience of the people of South Kuta, 2. Natural Resources showed a significant and positive influence on the economic resilience of the people of South Kuta, 3. Social Capital showed a positive influence but no significantly to the economic resilience of the South Kuta community, 4. Financial Capital shows a negative and significant influence on the economic resilience of the South Kuta community, 5. Economic Resilience has a simultaneous influence on Human Resources, Natural Resources, Social Capital, Financial Capital so that they become one unit in the South Kuta Community.  Implications of this research found: 1. Policies in developing Human Resources, 2. Sustainable Management of Natural Resources, 3. Strengthening Social Capital, 4. Access to Financial Capital, 5. Increasing economic readiness and adaptation, 6. Development of local initiatives.